2020
DOI: 10.1158/0008-5472.can-19-3326
|View full text |Cite|
|
Sign up to set email alerts
|

The EZH2–PHACTR2–AS1–Ribosome Axis induces Genomic Instability and Promotes Growth and Metastasis in Breast Cancer

Abstract: Aberrant activation of histone methyltransferase EZH2 and ribosome synthesis strongly associate with cancer development and progression. We previously found that EZH2 regulates RNA polymerase III-transcribed 5S ribosomal RNA gene transcription. However, whether EZH2 regulates ribosome synthesis is still unknown. Here we report that EZH2 promotes ribosome synthesis by targeting and silencing a long non-coding RNA PHACTR2-AS1 (PAS1). PHACTR2-AS1 directly bound ribosome DNA genes and recruited histone methyltrans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…In prostate cancer, it was reported that the elevated expression of SUV39H1 promotes cancer cell aggression [31] . In breast cancer, SUV39H1 binds to PHACTR2-AS1-30nt-RNA, silences DNA genes and then restrains breast cancer progression and lung metastasis in mice [32] . In malignant brain glioma, tumors can be suppressed by repressive targets of SUV39H1 [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, it was reported that the elevated expression of SUV39H1 promotes cancer cell aggression [31] . In breast cancer, SUV39H1 binds to PHACTR2-AS1-30nt-RNA, silences DNA genes and then restrains breast cancer progression and lung metastasis in mice [32] . In malignant brain glioma, tumors can be suppressed by repressive targets of SUV39H1 [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed the effects of FTO 77 , protein arginine methyltransferase 1 (PRMT1) 78 , coactivator associated arginine methyltransferase 1 (CARM1)/PRMT4 79 , Otubain-2 (OTUB2) 80 , RING finger protein 144A (RNF144A) 81 , plant homeodomain finger protein 20-like protein 1 (PHF20L1) 82 , heat shock transcription factor 1 (HSF1) 83 , epithelial cell transforming sequence 2 (ECT2) 84 , pescadillo homolog 1 (PES1) 85 , PHACTR2-AS1 (PAS1) 86 , breast cancer-related transcript 1 (BCRT1) 87 , and circCDYL 88 on progression of breast cancer and they provided novel therapeutic targets. TNBC is especially hard to treat due to the lack of targets.…”
Section: Novel Therapeutic Targets and New Drugsmentioning
confidence: 99%
“…It is differentially expressed in lung adenocarcinoma (47), and polymorphisms in the gene have been shown to affect DNA repair capacity, which is a risk factor for lung cancer (48). Long noncoding antisense RNA PHACTR2-AS1 has been shown to promote metastasis in breast cancer (49). Good potential causal variants were identified at rs966382235, rs79313503, and rs553447284.…”
Section: Candidate Genes -Utrn and Phactr2mentioning
confidence: 99%